Evaluating hospital performance in antibiotic stewardship to guide action at national and local levels in a lower-middle income setting. (13th December 2019) - McKnight, Jacob; Maina, Michuki; Zosi, Mathias; Kimemia, Grace; Onyango, Truphena; Schultsz, Constance; English, Mike; Tosas-Auguet, Olga
ABSTRACT: Background: Inappropriate use of antibiotics can lead to the development of resistant pathogens. Ensuring proper use of these important drugs in all healthcare facilities is essential. Unfortunately, however, very little is known about how antibiotics are used in LMIC clinical settings, nor to what degree antibiotic stewardship programmes are in place and effective. Objective: We aimed to record all Antibiotic Stewardship policies and structures in place in 16 Kenyan hospitals. We also wanted to examine the context of antibiotic-related practices in these hospitals. Methods: We generated a set of questions intended to assess the knowledge and application of antibiotic stewardship policies and practices in Kenya. Using a set of 17 indicators grouped into four categories, we surveyed 16 public hospitals across the country. Additionally, we conducted 31semi-structured interviews with frontline healthcare workers and hospital managers to explore the context of, and reasons for, the results. Results: Only one hospital had a resourced ABS policy in place. In all other hospitals, our survey teams commonly identified structures, resources and processes that in some way demonstrated partial or full control of antibiotic usage. This was verified by the qualitative interviews that identified common underlying issues. Most positively, we find evidence discipline-specific clinical guidelines have been well accepted and have conditioned and restricted antibiotic use. Conclusion: Only one hospital had an official ABS programme, but many facilities had existing structures and resources that could be used to improve antibiotic use. Thus, ABS Strategies should be built upon existing practices with national ABS policies taking maximum advantage of existing structures to manage the supply and prescription of antimicrobials. We conclude that ABS interventions that build on established responsibilities, methods and practices would be more efficient than interventions that presume a need to establish new ABS apparatus.